2008
DOI: 10.1086/587133
|View full text |Cite
|
Sign up to set email alerts
|

Kinemetry of SINS High‐Redshift Star‐Forming Galaxies: Distinguishing Rotating Disks from Major Mergers

Abstract: We present a simple set of kinematic criteria that can distinguish between galaxies dominated by ordered rotational motion and those involved in major merger events. Our criteria are based on the dynamics of the warm ionized gas (as traced by H) within galaxies, making this analysis accessible to high-redshift systems, whose kinematics are primarily traceable through emission features. Using the method of kinemetry (developed by Krajnović and coworkers), we quantify asymmetries in both the velocity and velocit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
361
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(381 citation statements)
references
References 76 publications
(167 reference statements)
18
361
1
1
Order By: Relevance
“…Collectively, they observe 16 SMGs at 2.0 < z < 2.5 and present strong evidence for merger-driven histories−many at an early stage first pass, where multiple components are seen separated by ∼8 kpc and 200 km s −1 , while others are later stage single-component systems with high-dispersion and buried AGN. Figure 29 illustrates the line-profile characteristics of these SMGs with respect to local starbursts from the SINGS sample, the z ∼ 2 SINS sample of star-forming galaxies (Shapiro et al, 2008), some simulated SMGs Davé et al (2010), and simulated disk and merger templates (also from Shapiro et al, 2008). The divide between mergers and disks is quite clear and narrow in this sample, with ∼8.5/10 of SMGs lying in the unambiguous merger-driven region of the plot.…”
Section: Kinematicsmentioning
confidence: 98%
See 2 more Smart Citations
“…Collectively, they observe 16 SMGs at 2.0 < z < 2.5 and present strong evidence for merger-driven histories−many at an early stage first pass, where multiple components are seen separated by ∼8 kpc and 200 km s −1 , while others are later stage single-component systems with high-dispersion and buried AGN. Figure 29 illustrates the line-profile characteristics of these SMGs with respect to local starbursts from the SINGS sample, the z ∼ 2 SINS sample of star-forming galaxies (Shapiro et al, 2008), some simulated SMGs Davé et al (2010), and simulated disk and merger templates (also from Shapiro et al, 2008). The divide between mergers and disks is quite clear and narrow in this sample, with ∼8.5/10 of SMGs lying in the unambiguous merger-driven region of the plot.…”
Section: Kinematicsmentioning
confidence: 98%
“…This figure is reproduced with permission from Alaghband-Zadeh et al (2012). Blue background points represent regions dominated by smoothly rotating disk galaxies while red points are expected to be dominated by merger-driven templates (Shapiro et al, 2008). The triangles represent local samples: both normal star-forming galaxies from SINGS (blue) and ULIRGs (yellow).…”
Section: Physical Size and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Forster Schreiber et al 2006;Shapiro et al 2008;Genzel & Burkert 2008;Mancini et al 2011;). In addition, many primordial spheroids that are forming the bulk of their stellar mass at z ∼ 2 do not show the tidal features that would be expected from recent major mergers ).…”
Section: Introductionmentioning
confidence: 99%
“…The SINS/zC-SINF and other near-IR IFU surveys of kinematics revealed that > 50% of z ∼ 1−3 SFGs are fairly regular rotation-dominated disks, whereas a minority consists of disturbed (major) merging systems or more compact, velocity dispersion-dominated objects (e.g., Shapiro et al 2008;Förster Schreiber et al 2009;Law et al 2009;Jones et al 2010b;Gnerucci et al 2011a;Épinat et al 2012;Newman et al 2013). The rotation velocity v rot scales roughly linearly with galaxy size, consistent with centrifugally-supported baryonic disks of constant angular momentum parameter within virialized dark matter halos.…”
Section: Kinematics and Structure Of Sfgs And Properties Of Disks Atmentioning
confidence: 99%